2017
DOI: 10.1007/s12599-017-0491-3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organization Size and Sector on Adopting Business Process Management

Abstract: The business process management (BPM) discipline is starting to recognize the importance of contextawareness. In spite of this recognition, few studies investigate the effect of diverse contextual factors on BPM. To fill this gap, the study statistically analyzes the effect of organization size and sector, as specific contextual factors, on the adoption of BPM. The latter is measured by means of BPM capabilities for which data was collected from 2309 employees in 72 organizations. The study relies on the Conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 34 publications
0
39
0
1
Order By: Relevance
“…To explain BPM phenomena in an organization, the BPM literature indicates mostly theories, which we also present in this study as the main theories underlying BPM adoption and enhancing understanding of BPM motivations [18,19].…”
Section: Motivations For Bpm Adoption: Initial Taxonomy Based On Onlimentioning
confidence: 96%
“…To explain BPM phenomena in an organization, the BPM literature indicates mostly theories, which we also present in this study as the main theories underlying BPM adoption and enhancing understanding of BPM motivations [18,19].…”
Section: Motivations For Bpm Adoption: Initial Taxonomy Based On Onlimentioning
confidence: 96%
“…Nonetheless, public sector organizations also profit from improving their processes and from digital process innovation to better serve their customers/tax payers. As argued by [5] context awareness is one of the ten principles of good BPM, and [40] provide evidence that the maturity of processes is generally lower in the public sector, which does not face the competitive pressure of the private sector. Nevertheless, even in the public sector, there are pockets of digital innovation and organisational ambidexterity, as documented by [41] in the IoT smart city projects.…”
Section: Process Management In the Public Sector (Challenge 3)mentioning
confidence: 97%
“…Finally, Saidani et al 32 distinguishes between a generic layer (i.e., describing the general characteristics of the context common to all business areas) and a specific layer (i.e., defining the details in specific business fields). Rosemann et al's 28 framework is the most extensive one, and it was used by other authors to situate their work 33,34 . This study is located in Rosemann et al's 28 immediate layer (i.e., business processes), internal layer (i.e., organization size), external layer (i.e., organization sector and organization competitiveness), and environmental layer (i.e., organization location).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Although only few context‐aware studies exist, organizational sector and size are mostly mentioned as contextual factors. Evidence can be found in survey studies 34,35 and case studies 36,37 . Van Looy and Van den Bergh 34 concluded that organization sector seems to affect the BPM adoption of an organization, whereas a statistical dependency could not be found for organization size.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation